Noninvasive Molecular Imaging Using Reporter Genes - Brader, Peter; Serganova, Inna; Blasberg, Ronald G. (Journal of Nuclear Medicine, 2013)
Noninvasive reporter gene imaging is a component of molecular imaging. Reporter imaging can provide noninvasive assessments of endogenous biologic processes in living subjects and can be performed using different imaging modalities. This review will focus on radionuclide-based reporter gene imaging as developed and applied in preclinical and clinical studies. Examples of different reporter systems are presented, with a focus on human reporter systems. Selected applications are discussed, including adoptive cell therapies, gene and oncoviral therapies, oncogenesis, signal pathway monitoring, and imaging drug treatment. Molecular imaging, and noninvasive reporter gene imaging in particular, are making important contributions to our understanding of disease development, progression, and treatment in our current era of molecular medicine and individualized patient care.